1995
DOI: 10.2527/1995.7371954x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent responses of rats to ergovaline derived from endophyte-infected tall fescue

Abstract: Ergovaline, found in Acremonium coenophialum-infected tall fescue, is considered to be responsible for many symptoms associated with fescue toxicosis. Rats were tested to determine time-related thermoregulatory responses to acute treatment with ergovaline during specific thermal challenges. Isolated ergovaline was administered to rats (15 micrograms/kg body mass, i.p.) at controlled ambient temperatures (Ta) of 7 to 9 degrees C (cold) and 31 to 33 degrees C (hot). Treatment at cold Ta resulted in a decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 0 publications
6
27
0
Order By: Relevance
“…Thus, the hyperthermia-rectifying effect of M+, when combined with E+, was likely due to the suppression of endogenous NO production. Spiers et al (1995) reported indirect evidence of a compromise in peripheral vasculature by ergovaline injection in rats subjected to HS, as evidenced by the rise in rectal temperature accompanying a decline in tail temperature.…”
Section: Article In Pressmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, the hyperthermia-rectifying effect of M+, when combined with E+, was likely due to the suppression of endogenous NO production. Spiers et al (1995) reported indirect evidence of a compromise in peripheral vasculature by ergovaline injection in rats subjected to HS, as evidenced by the rise in rectal temperature accompanying a decline in tail temperature.…”
Section: Article In Pressmentioning
confidence: 96%
“…Administration of ergopeptine alkaloids under thermoneutral or cold conditions, results in a decrease in core body temperature (Spiers et al, 1995(Spiers et al, , 2005a, that is due to a reduction in metabolic heat production (Spiers et al, 1995). In contrast, similar treatment during heat stress (HS) induces hyperthermia above the control level (Spiers et al, 1995(Spiers et al, , 2005a.…”
Section: Introductionmentioning
confidence: 98%
“…This central effect upon body temperature occurs at a lower dosage compared to that necessary to mediate vasoconstriction. Spiers et al (1995) investigated the effects of injecting rats with ergovaline in both a…”
Section: Discussionmentioning
confidence: 99%
“…Serotonergic-2 receptors have also been shown to be involved in bronchoconstriction in calves (Linden et al 1993). Vasoconstriction of the peripheral vasculature by ergovaline interacting with adrenergic and serotonergic receptors results in a decreased ability to dissipate body heat and can contribute to increased core temperature (Spiers et al 1995). Foote et al (2013) indicated that ergovaline-induced vasoconstriction at the rumen epithelium may affect nutrient absorption, and hypothesised that this may affect intake as well as liveweight gain.…”
Section: (2) Vasoconstrictionmentioning
confidence: 99%